1999
DOI: 10.1002/pen.11393
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the addition of a low profile additive on the curing shrinkage of an unsaturated polyester resin

Abstract: Composites made of glass fibers and unsaturated polyester resins are widely applied for various products. The failure processes of such composites are insufficiently understood. Fracture of the resin often initiates bulk composite fracture. Residual stresses occur during the curing of the resin due to the resin volumetric shrinkage. These unfavorable stresses may enhance resin fracture. Moreover, resin shnnkage may decrease the surface quality of the product. The addition of Low Profile Additives &PA) to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The LSA can be divided into polar LSA, weak polar LSA and nonpolar LSA, and polar LSA exhibits the most efficient antishrinkage effect among them . The previous researches showed that in the application of polar LSA, the small temperature gradient in the curing process caused insufficient thermal expansion, and the mechanical properties of the composite materials were deteriorated …”
Section: Introductionmentioning
confidence: 99%
“…The LSA can be divided into polar LSA, weak polar LSA and nonpolar LSA, and polar LSA exhibits the most efficient antishrinkage effect among them . The previous researches showed that in the application of polar LSA, the small temperature gradient in the curing process caused insufficient thermal expansion, and the mechanical properties of the composite materials were deteriorated …”
Section: Introductionmentioning
confidence: 99%
“…The effect of different types of LPA on the cure shrinkage was investigated by many researchers [13, 21, 23, 29–33]. It was determined that there is an optimal LPA content to compensate for cure shrinkage that varies depending on the resin and LPA systems studied.…”
Section: Introductionmentioning
confidence: 99%
“…Because there is large difference in thermal expansion coefficients between the two materials (the thermal expansion coefficient of the plastic film is about 10 times of that of the flexible decorative veneer) and the two materials are relatively thin, the shrinkage displacement, and the internal stress in the two material generated during hot pressing, pressure relief, and cooling processes are uneven extremely, so that warpage may occur on the side of the plastic film with a large thermal expansion coefficient in the composite flexible decorative material, 8–11 and warpage has direct effects on industrial application of the flexible decorative veneer on surface of wood products. Therefore, how to control warpage during hot pressing and compositing processes in application of PRPDSV is the key technical difficulty to be solved for industrial production and application of the product 12–17 …”
Section: Introductionmentioning
confidence: 99%